204k views
4 votes
Explain how to write an equivalent expression for the expression 3(4x + 2y) + 5x. Be sure to explain which properties you used. What method can you use to prove the 2 expressions are equivalent?

1 Answer

2 votes

Answer:

Using multiplicative and additional property .

= 17x +6y

Explanation:

3(4x + 2y) + 5x.

Multiplicative property.

Using 3 to multiply what's inside the bracket.

= 3*4x + 3*2y +5x

= 12x + 6y +5x

Addition property.

Collection of all like terms together.

All values with same alphabets are going to be added together

= 12x +5x +6y

= 17x +6y

To prove if 3(4x + 2y) + 5x.= 17x +6y

Let's assume both x and y to be 1

We have

3(4(1) + 2(1)) + 5(1) = 17(1) + 6(1)

3(6)+5=17 +6

23= 23.

Proved.

User Ryan Kohn
by
5.2k points